The design of Indonesian SARS‐CoV‐2 primers based on phylogenomic analysis of the SARS‐CoV‐2 clades - Tsania Taskia Nabila; Ata Rofita Wasiati; Afif Pranaya Jati; Annisa Khumaira (Universitas Gadjah Mada, 2022)
Molecular detection needs to be augmented for COVID‐19 detection in Indonesia using the PCR method with primer‐based gene analysis. This is necessary because the RNA of the SARS‐CoV‐2 virus, the causative infectious agent of the pandemic, has been mutated. Therefore, this study aimed to develop a primer design for determining SARS‐CoV‐2 clades in Indonesia using phylogenomic analysis. Data were obtained from 38 GISAID (Global Initiative on Sharing All Influenza Data) viruses and the relationships were analyzed using maximum likelihood (ML) phylogenomic analysis with a substitution model of generalized time‐reversible (GTR) to construct the tree topology. The results showed that the five types of SARS‐CoVs‐2 clades in Indonesia were L, G, GH, GR, and O. It also indicated that the GH region had the highest rate of clade at 50%, with the S clade affecting its formation. Furthermore, the genome sequences of the GH type used to design its primer were based on three genes, namely RdRp, S, and N. The RdRp and N genes were found to be conserved and hardy mutants, while the S gene occurred repeatedly. Several previous studies have stated that the designed primers produced missense mutations compared to another in silico. Therefore, three sets of primers were achieved from the GC contents and clamps, Tm range, and structural secondary indicator standards.